The tapetal tissue is essential for the maintenance of redox homeostasis during microgametogenesis in tomato. (19th November 2022) - Salazar‐Sarasua, Blanca; López‐Martín, María Jesús; Roque, Edelín; Hamza, Rim; Cañas, Luis Antonio; Beltrán, José Pío; Gómez‐Mena, Concepción
SUMMARY: The tapetum is a specialized layer of cells within the anther, adjacent to the sporogenous tissue. During its short life, it provides nutrients, molecules and materials to the pollen mother cells and microsporocytes, being essential during callose degradation and pollen wall formation. The interaction between the tapetum and sporogenous cells in Solanum lycopersicum (tomato) plants, despite its importance for breeding purposes, is poorly understood. To investigate this process, gene editing was used to generate loss‐of‐function mutants that showed the complete and specific absence of tapetal cells. These plants were obtained targeting the previously uncharacterized Solyc03g097530 ( SlTPD1 ) gene, essential for tapetum specification in tomato plants. In the absence of tapetum, sporogenous cells developed and callose deposition was observed. However, sporocytes failed to undergo the process of meiosis and finally degenerated, leading to male sterility. Transcriptomic analysis conducted in mutant anthers lacking tapetum revealed the downregulation of a set of genes related to redox homeostasis. Indeed, mutant anthers showed a reduction in the accumulation of reactive oxygen species (ROS) at early stages and altered activity of ROS‐scavenging enzymes. The results obtained highlight the importance of the tapetal tissue in maintaining redox homeostasis during male gametogenesis in tomato plants. Significance Statement: During anther development, the tapetal cells that surround the sporocytes have essential roles in male meiotic progression and the formation of mature pollen grains. In tomato, despite its importance for breeding purposes, the interaction between the tapetum and sporogenous tissues is poorly understood. Here we report the generation of tomato plants devoid of tapetum by the mutation of a previously uncharacterized gene Solyc03g097530 ( SlTPD1 ). Transcriptomic and physiological analyses of the mutant plants revealed the critical role of the tapetal tissue in maintaining redox homeostasis during male gametogenesis.